Zmiany w rentowności produkcji rolniczej w kontekście możliwości wdrażania zasad logistyki na przykładzie branży drobiarskiej - Szpon, Jakub (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Polish integration with EU members forces very deep transformation of Polish agriculture. High market competitiveness is rearranged on profitability of production decrease and it indirectly enforces cultivators to restructure and modernize lead activity. Except investment cost made in agriculture sector, modern logistic concepts improving production process organization and cost optimalization should be introduced. Introducing logistics rules is particularly advisable in intensive production, e.g. in poultry branch. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 230-236